THE RELATIONSHIP OF ALCOHOL PROBLEMS TO RISK FOR UNIDIRECTIONAL AND BIDIRECTIONAL INTIMATE PARTNER VIOLENCE AMONG A SAMPLE OF BLUE-COLLAR COUPLES - Cunradi, Carol B. (2011)
Understanding how each partner's alcohol problems may contribute to the risk of male-to-female only, female-to-male only, or bidirectional partner violence is important for prevention and treatment of these problems. Multinomial regression analysis was conducted using data from 848 blue-collar couples. Findings suggest that male alcohol problems are linked with male-to-female and bidirectional partner violence, but not to female-to-male partner violence. Female alcohol problems do not appear to be related to any type of partner aggression. Each partner's level of impulsivity was associated with bidirectional partner violence. Male impulsivity was associated with male-to-female violence, and female impulsivity was associated with female-to-male violence. Prevention of male alcohol problems and promotion of non-confrontational conflict solving techniques may help reduce partner aggression among couples in the general household population.